Rise up : confronting a country at the crossroads - Sharpton, Al (Hanover Square Press, 2020)
The respected civil rights leader and host of "PoliticsNation" presents a rousing call to action that examines the administrations of Barack Obama and Donald Trump while heralding the movements that have emerged in response to today's political turbulence.